Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Using the method of partial fractions, determine the following integral: integral ((8x - 23)/(x^2 - 5x + 4))dx?
Using the method of partial fractions, determine the following integral:
integral ((8x - 23)/(x^2 - 5x + 4))dx
Thank you
3 Answers
- Chandler BingLv 69 years agoFavorite Answer
(8x-23)/(x²-5x+4) = (8x-23)/(x-1)(x-4)
(8x-23)/(x-1)(x-4) = A/(x-1) + B/(x-4)
(8x-23)/(x-1)(x-4) = [A(x-4) + B(x-1)]/(x-1)(x-4)
(8x-23)/(x-1)(x-4) = [(A+B)x-(4A+B)]/(x-1)(x-4)
==> 8x-23 = (A+B)x -(4A+B)
Matching the coefficients, you get
A+B = 8
4A+B = 23
Solving these simultaneously, you find
A = 5, B = 3
So
(8x-23)/(x²-5x+4) = 5/(x-1)+ 3/(x-4)
∫(8x-23)dx/(x²-5x+4)=∫[5/(x-1)+ 3/(x-4)] dx
= 5∫dx/(x-1) + 3∫dx/(x-4)
= 5ln|x-1| + 3ln|x-4| + C
- Anonymous9 years ago
First factor the denominator:
x^2-5x +4 = (x-4)(x-1)
Now set up the summation of each part:
A/(x-4) +B/(x-1) = ((8x - 23)/(x^2 - 5x + 4))
If you combine the denominators on the left hand side (LHS) you get:
(A(x-1) +B(x-4))/(x^2 - 5x + 4) = ((8x - 23)/(x^2 - 5x + 4))
Now you can cancel the denominators and expand the LHS to get:
Ax -A + Bx -4B = 8x-23
or rearranging:
(A+B)x + (-A - 4B) = 8x-23
Now you have 2 equations to solve for A and B.
A +B = 8,
-A-4B = -23
Solve the first for A
A=8-B
Plug into the second to solve for B
-(8 -B) -4B = -23
-3B = -15
B=5
Plugging back into the first,
A=3
Now you can plug 3 and 5 in above for A and B to get
3/(x-4) + 5/(x-1) = ((8x - 23)/(x^2 - 5x + 4))
and you have your new integral, the solution to which is
3 ln(x-4) + 5 ln(x-1)
Source(s): My Mind - Anonymous5 years ago
(x^2-1)/ (9x^2+6x+5)^2 = A/(9x^2+6x+5) + Bx+C/(9x^2+6x+5)^2 Solving you will get A= 1/9 , B= -2/3 and C= -14/9 -1/54 (9x+1)/(9x^2+6x+5) -1/108 arctan ((3x+1)/2)+C